Japan Trench event stratigraphy: First results from IODP giant piston coring in a deep-sea trench to advance subduction zone paleoseismology - Michael Strasser; Ken Ikehara; Charlotte Pizer; Takuya Itaki; Yasufumi Satoguchi; Arata Kioka; Cecilia McHugh; Jean-Noel Proust; Derek Sawyer; J. Everest; L. Maeda; K. Hochmuth; et al. (Marine Geology, 2024)

Guidelines on reporting treatment conditions for emerging technologies in food processing - Vicente M. Gómez-López; Gianpiero Pataro; Brijesh Tiwari; Mario Gozzi; María Ángela A. Meireles; Shaojin Wang; Buenaventura Guamis; Zhongli Pan; Hosahalli Ramaswamy; Sudhir Sastry; Florent Kuntz; Patrick J. Cullen; et al. (Critical Reviews in Food Science and Nutrition, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Epistemological dimensions of the water–energy–food nexus approach: reply to discussions of “Challenges in operationalizing the water–energy–food nexus” - C. Cudennec; J. Liu; J. Qi; H. Yang; C. Zheng; A. K. Gain; R. Lawford; L. de Strasser; P. T. Yillia (Hydrological Sciences Journal, 2018)

Uncoupled eNOS annihilates neuregulin-1β-induced cardioprotection: a novel mechanism in pharmacological postconditioning in myocardial infarction - Bernd Ebner; Stefan A. Lange; Thomas Eckert; Clementine Wischniowski; Annette Ebner; Rüdiger C. Braun-Dullaeus; Christof Weinbrenner; Carsten Wunderlich; Gregor Simonis; Ruth H. Strasser (Molecular and Cellular Biochemistry, 2013)

Increased P2X7R expression in atrial cardiomyocytes of caveolin-1 deficient mice - K. Barth; C. Pfleger; A. Linge; J. A. Sim; A. Surprenant; N. Steinbronn; R. H. Strasser; M. Kasper (Histochemistry and Cell Biology, 2010)

Limited genetic variation and structure in softshell clams (Mya arenaria) across their native and introduced range - C. A. Strasser; P. H. Barber (Conservation Genetics, 2009)

Foodborne outbreak of hepatitis A, November 2007–January 2008, Austria - D. Schmid; R. Fretz; G. Buchner; C. König; H. Perner; R. Sollak; A. Tratter; M. Hell; M. Maass; M. Strasser; F. Allerberger (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Association of OPRM1 A118G variant with the relative reinforcing value of nicotine - R. Ray; C. Jepson; F. Patterson; A. Strasser; M. Rukstalis; K. Perkins; K. G. Lynch; S. O’Malley; W. H. Berrettini; C. Lerman (Psychopharmacology, 2006)